2013
DOI: 10.1080/14786419.2012.722088
|View full text |Cite
|
Sign up to set email alerts
|

A new antifeedant clerodane diterpenoid fromTinospora cordifolia

Abstract: Phytochemical investigation of the chloroform extract of Tinospora cordifolia yielded a new clerodane diterpenoid tincordin along with tinosporide, 8-hydroxytinosporide, columbin, 8-hydroxycolumbin and 10-hydroxycolumbin. The structure of the new compound was elucidated comprehensively using 1D and 2D NMR methods. All major clerodane diterpenoids isolated were tested for their efficacy as insect antifeedants against Earias vitella, Plutella xylostella and Spodoptera litura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The most studied biological property of clerodane-type diterpenes is the insect antifeedant activity [ 104 ]. Clerodane diterpenes such as tincordin ( 50 ), tinosporide ( 51 ), 8-hydroxytinosporide ( 52 ), columbin ( 53 ), 8-hydroxycolumbin ( 54 ), and 10-hydroxycolumbin ( 55 ) ( Figure 23 ) were evaluated for their efficacy as insect antifeedants against Earias vittella , Plutella xylostella , and Spodoptera litura [ 105 ]. All diterpenes showed antifeedant activity and compound 52 was the most effective one [ 105 ].…”
Section: Toxicity Of Diterpenesmentioning
confidence: 99%
“…The most studied biological property of clerodane-type diterpenes is the insect antifeedant activity [ 104 ]. Clerodane diterpenes such as tincordin ( 50 ), tinosporide ( 51 ), 8-hydroxytinosporide ( 52 ), columbin ( 53 ), 8-hydroxycolumbin ( 54 ), and 10-hydroxycolumbin ( 55 ) ( Figure 23 ) were evaluated for their efficacy as insect antifeedants against Earias vittella , Plutella xylostella , and Spodoptera litura [ 105 ]. All diterpenes showed antifeedant activity and compound 52 was the most effective one [ 105 ].…”
Section: Toxicity Of Diterpenesmentioning
confidence: 99%
“…It inhibits the growth of cancer causing microorganisms, inhibit oncogenes and the enzymes related to carcinogenesis [29][30]. Tinocordin, columbin, 8-hydroxycolumbin, 10-hydroxycolumbin are diterpeniod lactones reported in Chloroform extract of T. cordifolia [12]. Another diterpenoid epoxy clerodane from chloroform: methanol extraction of alcoholic extract of T. cordifolia has been reported to possess anti-cancer activity against hepatocellular carcinoma induced by diethylnitrosamine [24].…”
Section: Discussionmentioning
confidence: 99%
“…Formulations of T. cordifolia extract with turmeric are effective in preventing hepatotoxicity [11]. Some recent studies have shown anti-feedent activity of clerodane glycosides isolated from chloroform extract of T. Cordifolia along with anti-cancer activity [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the higher concentration of the clerodane diterpenoids in younger leaves and insect anti-feedant activities of various clerodanes (Sosa et al , 1994; Klein Gebbinck et al , 2002; Rosselli et al , 2004; Sivasubramanian et al , 2013) suggest that they may serve to protect young susceptible tissues from herbivore attack.…”
Section: Discussionmentioning
confidence: 99%